Transcriptome analysis reveals adaptation mechanism of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) adults to benzoquinone stress. (March 2023) - Guo, Yafei; Lü, Jianhua; Bai, Chunqi; Gu, Chengcai; Guo, Chao
Abstract: Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) is a cosmopolitan pest of stored grain. The secretions of the stink gland of T. castaneum contain benzoquinone, which acts as immune defense substances. However, high concentrations of secretions can be harmful to the individuals. The effects of benzoquinone produced by T. castaneum and the addition of benzoquinone to its living environment on T. castaneum were investigated, and the transcriptome of T. castaneum adults was analyzed to explore molecular mechanism of environmental adaptation of T. castaneum under benzoquinone stress by using Illumina sequencing technology. A total of 5361, 6923, and 83 differentially expressed genes were respectively identified in T. castaneum adults in different treated wheat flour (adults in T. castaneum infested wheat flour (referred to as T2) vs Control (adults in clear wheat flour, referred to as T1), adults in wheat flour with benzoquinone (referred to as T3) vs Control (T1), and T3 vs T2). We identified 2562 commonly up-regulated genes and 1931 commonly down-regulated genes in T2 vs T1 and T3 vs T1 treatments. Weighted gene co-expression network analysis (WGCNA) identified 6 modules composing of differentially co-expressed genes. The Turquoise module was extremely associated with the T2 sample. Turquoise module of genes was found to be highly correlated with the oxidation-reduction process (168 genes), macromolecular complex (154 genes), and oxidoreductase activity (169 genes). Three transcription factor genes, LOC664577, LOC661810, and LOC657046 were presented in Turquoise module as hub genes. The changes in gene expression indicated that T. castaneum may transfer toxic compounds into low-toxicity or non-toxic products through a variety of enzymes in response to benzoquinone stress. The current results provide the molecular mechanisms that may explain the adaptation of T. castaneum to benzoquinone stress. Highlights: A total of 5361, 6923, and 83 differentially expressed genes were respectively identified in T. castaneum adults in different treated wheat flour. Three transcription factor genes were presented in Turquoise module as hub genes. T. castaneum may transfer toxic compounds into low-toxicity or non-toxic products in response to benzoquinone stress.